1989
DOI: 10.1038/sc.1989.27
|View full text |Cite
|
Sign up to set email alerts
|

Microangiographic study of spinal cord injury and myelopathy

Abstract: SummaryPost-mortem microangiography has been performed in 12 patierUs with traumatic cervical cord injury, 2 patients with myelopathy, and one patient with post traumatic syringomyelia.Microangiography defined 4 zones in the injured spinal cord. In traumatic injury, the size and extent of the non-filling area (Zone 1) was directly related to the injury force. Subsequently these areas became cavitated. Surrounding the non-filling area, widely extending areas demonstrated filling of capillaries but showed damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Tissue edema is one of the main causes of secondary damage after SCI (Shingu et al, 1989;Blight, 1991;Popovich et al, 1996;Tator & Koyanagi, 1997;Mautes et al, 2000;Bilgen et al, 2001;Westergren et al, 2001;Casella et al, 2002;Loy et al, 2002;Narayana et al, 2004;Maikos & Shreiber, 2007). Although application of VEGF after SCI increases vascular permeability and tissue edema in the spinal cord, deterioration of functional recovery has not been reported (Patel et al, 2009;Sundberg et al, 2010).…”
Section: Vegf-r1 Affects Vascular Permeability But Not Long-term Conmentioning
confidence: 99%
“…Tissue edema is one of the main causes of secondary damage after SCI (Shingu et al, 1989;Blight, 1991;Popovich et al, 1996;Tator & Koyanagi, 1997;Mautes et al, 2000;Bilgen et al, 2001;Westergren et al, 2001;Casella et al, 2002;Loy et al, 2002;Narayana et al, 2004;Maikos & Shreiber, 2007). Although application of VEGF after SCI increases vascular permeability and tissue edema in the spinal cord, deterioration of functional recovery has not been reported (Patel et al, 2009;Sundberg et al, 2010).…”
Section: Vegf-r1 Affects Vascular Permeability But Not Long-term Conmentioning
confidence: 99%
“…Regenerative attempts within the central nervous system (CNS) after trauma have been suggested to be limited by many factors, including the lack of an adequate blood supply (Goldsmith et al, 1985; de la Torre and Goldsmith, 1988, 1990; Shingu et al, 1989; Goldsmith, 1994; Zhang and Guth, 1997). However, increased vessel densities have been described at various intervals after SCI in cats (Means et al, 1978; Beggs and Waggener, 1979), guinea pigs (Blight, 1991), rats (Zhang and Guth, 1997; Imperato‐Kalmar et al, 1997), and humans (Shingu et al, 1989). Studies of BSB permeability dynamics by using quantitative autoradiography have suggested that the injured spinal cord vasculature actually remains in a state of active remodeling until at least 28 days postcontusive injury (Popovich et al, 1996).…”
mentioning
confidence: 99%
“…It is therefore not surprising that major therapeutic efforts have been directed towards slowing down or reversing the progression of secondary events in SCI (Bradbury and McMahon, 2006;Rossignol et al, 2007). Dynamic vascular changes are thought to play an important role in the evolution of secondary injury in SCI (Shingu et al, 1989;Blight, 1991;Popovich et al, 1996;Tator and Koyanagi, 1997;Mautes et al, 2000;Westergren et al, 2001;Casella et al, 2002;Loy et al, 2002;Narayana et al, 2004;Maikos and Shreiber, 2007). Among others, some of the specific vascular changes include angiogenesis and disruption of the blood-spinal cord barrier (BSCB).…”
mentioning
confidence: 99%